The Combined and Differential Effects of Monophasic and Biphasic Repetitive Transcranial Magnetic Stimulation on ERP-Indexed Attentional Processing in Treatment-Resistant Depression - Hyde, Molly (Université d'Ottawa / University of Ottawa, 2019)
In addition to low mood, major depressive disorder (MDD) is characterized by persistent cognitive deficits that impair daily functioning and resist improvement with conventional pharmacotherapies. Repetitive transcranial magnetic stimulation (rTMS) holds promise as an efficacious alternative, offering better outcomes than medication for patients with treatment-resistant depression (TRD). Yet, current rTMS protocols that administer sinusoidal biphasic pulses achieve remission in less than the majority. However, monophasic pulses may yield higher success rates based on greater cortical excitation/neuromodulation strength. MDD is associated with altered P300 event-related potentials (ERPs), indexing decreased attentional resource allocation and slower cortical processing speed. Using a cohort of 20 TRD patients who received high-frequency rTMS, this study aimed to assess the impact of monophasic and biphasic stimulation on attention-related P300 measures and their utility as correlates of clinical/cognitive response. Based on baseline and post-treatment change in P300 components, rTMS-induced increases in automatic attention/passive information processing differed by pulse type and predicted greater clinical improvement in depressed individuals. This study represents an important step towards identifying cognitive changes and underlying cortical mechanisms associated with rTMS response and targeted MDD treatment.
Keywords: Event-related potential; Major depressive disorder; Monophasic; Repetitive transcranial magnetic stimulation; Treatment-resistant depression; P300